Pengaruh Pelatihan Digital Branding Terhadap Hasil Penjualan UMKM di Desa Kajang Kec Sawahan Kab Madiun - Anisa, Anisa; Widodo, Widodo (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2024)
This research discusses the influence of digital branding training on UMKM sales results in Kajang Village, District. Sawahan District. Madiun. The training studied had occurred so that the researcher used an ex post facto comparative quantitative approach as the research method used. Apart from that, the data collection technique is through distributing questionnaires that have been tested. The data analysis techniques used are validity test, reliability test, normality test, paired sample test and product moment correlation test. The results of the research show that there is an influence of digital branding training on the sales results of UMKM in Kajang village, Sawahan subdistrict, Madiun district. This is proven by the results of the t count calculation and the paired sample t test which shows that if the t count value is 9,683 it is greater than the t table value with N-2= 31 (29) which is 0.3550, apart from that it is based on the results of observational data on the calculation of sales results. products before training and after training there was an increase of 36%. So it can be concluded that the digital branding training carried out by Kajang village was successful as seen from the increase in the number of products sold.